(untitled) (Global Journal of Science Frontier Research, 2019)
The study was conducted to determine the effect hematological indices and serum biochemistry of Sheep fed a rich diet supplemented with graded level of exogenous enzyme in the semi-arid region of Nigeria. Twenty Sheep of the non-descript breed used for the study. The animals were weighed, and divided into four groups. Each group of 5-animals randomly allotted to one of the 4-treatments in a Completely Randomized Design. The exogenous enzyme included in the diets at the level of 0, 200, 400, and 600g in TI, (Control), T2, T3 and T4, respectively. The result showed that PCV, Hb, WBC, and Neutrophil differed considerably (P0.05) different between the treatments. There were significant (P0.05) among the treatment groups. However, the level of inclusion of an exogenous enzyme at 400g/100kg of corn cob based diets showed the best result. The utilization of the corn cob based diet treated with exogenous enzyme, had no deleterious effect on the health condition as demonstrated by the serum biochemical and hematological parameters of the Sheep.